Siponimod vs placebo in active secondary progressive multiple sclerosis: a post hoc analysis from the phase 3 EXPAND study - Gold, Ralf; Piani-Meier, Daniela; Kappos, Ludwig; Bar-Or, Amit; Vermersch, Patrick; Giovannoni, Gavin; Fox, Robert J.; Arnold, Douglas L.; Benedict, Ralph H. B.; Penner, Iris-Katharina; Rouyrre, Nicolas; Kilaru, Ajay; et al. (Journal of neurology, 2022)
Background Siponimod is a sphingosine 1-phosphate receptor modulator approved for active secondary progressive multiple sclerosis (aSPMS) in most countries; however, phase 3 EXPAND study data are from an SPMS population with/without disease activity. A need exists to characterize efficacy/safety of siponimod in aSPMS. Methods Post hoc analysis of participants with aSPMS (≥ 1 relapse in 2 years before study and/or ≥ 1 T1 gadolinium-enhancing [Gd +] magnetic resonance imaging [MRI] lesions at baseline) receiving oral siponimod (2 mg/day) or placebo for up to 3 years in EXPAND. Endpoints: 3-month/6-month confirmed disability progression (3mCDP/6mCDP); 3-month confirmed ≥ 20% worsening in Timed 25-Foot Walk (T25FW); 6-month confirmed improvement/worsening in Symbol Digit Modalities Test (SDMT) scores (≥ 4-point change); T2 lesion volume (T2LV) change from baseline; number of T1 Gd + lesions baseline–month 24; number of new/enlarging (N/E) T2 lesions over all visits. Results Data from 779 participants with aSPMS were analysed. Siponimod reduced risk of 3mCDP/6mCDP vs placebo (by 31%/37%, respectively; p < 0.01); there was no significant effect on T25FW. Siponimod increased likelihood of 6-month confirmed SDMT improvement vs placebo (by 62%; p = 0.007) and reduced risk of 6-month confirmed SDMT worsening (by 27%; p = 0.060). Siponimod was associated with less increase in T2LV (1316.3 vs 13.3 mm 3 ; p < 0.0001), and fewer T1 Gd + and N/E T2 lesions than placebo (85% and 80% reductions, respectively; p < 0.0001). Conclusions In aSPMS, siponimod reduced risk of disability progression and was associated with benefits on cognition and MRI outcomes vs placebo. Trial registration ClinicalTrials.gov number : NCT01665144.